Development and Validation of New High Performance Liquid Chromatography Analytical Technique For Separation of Diclofenac Sodium and Lidocaine Hydrochloride From Ampoule Injection - Salih, Mohammed Ali; Fattah Aziz, Dlivan; Ibrahim Ali, Salar (Kurdistan Journal of Applied Research, 2020)
In the current investigation, a number of chromatographic methods with the accurate, precise and specific criteria have been developed and validated for diclofenac sodium and lidocaine hydrochloride Commitment of their large quantities ampule of pharmaceutical dosage form. The High-Performance Liquid Chromatography (HPLC) system was performed at 25 ° C; with appropriate chromatographic isolation accomplished through the use of Waters Symmetry SB-C7 column with a mobile phase containing 0.1 M sodium acetate and methanol (40:60) (v/v). During development the portable stage was delivered at a stream rate of 1 mL/min, the wavelength was adjusted at 254 nm. First of all, the retention times for diclofenac sodium and lidocaine HCl were about 4.1 and 10.8 min accordingly. A performance and technical demonstration of the suggested Revers phase-HPLC method has been numerically challenged with support to process appropriateness, verticality, scales, simplicity, repeatability, sensitivity, stability, discovery and limits of quantification. In addition, the calibration curves for diclofenac sodium active pharmaceutical ingredient (API) with linear regressions > 0,999895 obtained linear in the distances 1870-5600 ?g / mL. Moreover, for determining of lidocaine HCl drug, a range of 500 - 1500 ?g/mL of working standard was used, the result showed for lidocain HCl that a linear curve with correlation coefficients of > 0.99980. Finally, the both drugs were isolated and resolute with selective and stable characteristics by the proposed technique. In the conclusion, successful validation of the HPLC approach has been demonstrated with high precision and accuracy for the assessment of both the mixed dosage form type of both diclofenac sodium and lidocaine HCl.